Pengaruh Ketidakamanan Kerja Terhadap Kinerja Karyawan Yang Dimediasi Oleh Kesejahteraan Subjektif : Peran Modal Psikologis Sebagai Pemoderasi - Aprilria, Irene Paskah Aprilria; Kurniasih, Retno (Awatara Publisher, 2025)
Job insecurity can have a significant impact on employee performance, especially in the highly competitive hospitality industry. This study aims to analyze the effect of job insecurity on employee performance mediated by subjective well-being and examine the role of psychological capital as a moderator. The method used is a quantitative approach with a survey and convenience sampling technique on employees of ASTON Purwokerto Hotel & Convention Center. The sample consisted of 45 respondents. Testing with Linear Regression Analysis, Sobel Test, and Residual Method showed that: (1) Job insecurity has a negative effect on employee performance, (2) Job insecurity has a negative effect on subjective well-being, (3) Subjective well-being has a positive effect on employee performance, (4) Subjective well-being mediates the relationship between job insecurity and employee performance, and (5) Psychological capital moderates the relationship between job insecurity and subjective well-being. Psychological capital is proven to strengthen the relationship. The implications of this study indicate that companies need to pay attention to employee well-being and develop training programs that improve employee psychological capital to improve performance. This study provides important insights for hotel owners in creating a better work environment.